Individual Capability and Effort in Retirement Benefit Choice. Issue 2 (24th August 2016) - Bateman, Hazel; Eckert, Christine; Iskhakov, Fedor; Louviere, Jordan; Satchell, Stephen; Thorp, Susan
Abstract: We investigate the role of individual capability and effort in the management of retirement ruin. In an experimental setting, we analyze how 854 defined contribution (DC) plan members reallocated wealth between a lifetime annuity and a phased withdrawal account when we increased the risk of exhausting the phased withdrawal account before the end of life. We find that more numerate individuals who put effort into understanding product features chose more longevity insurance at higher ruin risks. Financially literate members were more likely to show understanding of the product features, but general financial literacy did not directly improve ruin risk management. Initiatives aiming to help DC members understand income stream products at the time of the decision are warranted.